DISC HERNIATIONS AND NEURAL STRUCTURES COMPRESSION IN DIFFERENT LUMBOSACRAL TRANSITIONAL ANATOMY TYPES - Matveeva Niki; Chabukovska Radulovska Jasmina; Petrovska Tanja; Zhivadinovikj Julija; Zafirova Biljana (Faculty of Medicine, Ss.Cyril and Methodius University in Skopje, R. North Macedonia, 2021)
Introduction. Several studies describe the relationship between different lumbosacral transitional vertebra (LSTV) types, disc herniations and neural structures compression in the central and nerve root canal. The objective of this study was to evaluate the relationship between different LSTV groups and disc herniations associated with the grade of neural structures compression in the central and nerve root canal at transitional and at adjacent proximal to LSTV level. Material and methods. A total of 145 patients with lumbosacral radicular syndrome who underwent MRI examination of the lumbar spine were retrospectively analyzed. The study group comprised 75 patients who presented with LSTV, divided into four subgroups based on Castellvi classification. Seventy patients without LSTV were assigned to the control group. Results. There were significantly more disc herniations at the L/S junction in the study LSTV group compared to the control group (78.7 % vs 59.4%, p=.012). In the LSTV group more severe cauda equina and bilateral subarticular nerve root compression at the L/S junction was found (9%, p=.002) compared to the control group. Among the LSTV subgroups, more cauda equina compression was observed mainly in bilateral osseus and bilateral combined fusion group (57%, 54% vs 26%; p=.009, p=.012). At the adjacent proximal level severe cauda equina compression was significantly increased in the LSTV compared to the control group (34.7% vs 21.4%; p=.038). Among the LSTV subgroups severe cauda equina compression was most prevalent in bilateral articular fusion subgroup (42% vs 21%; p=.028). Conclusion. LSTV restrict the spinal segment mobility and transfer the external stress factors to the ipsilateral anomalous articulation, to the contralateral facet joint at the level of unilateral transition and to the spine fully mobile segments proximal to bilateral osseous or articulated fusion. These levels become high stress zones predisposing the occurrence of massive, large disc herniations associated with severe neural structures compression.
Keywords: Lumbosacral transitional vertebra; MRI; disc herniation; cauda equine; nerves; spinal